2023
DOI: 10.3390/su15076016
|View full text |Cite
|
Sign up to set email alerts
|

The Adoption of Robo-Advisory among Millennials in the 21st Century: Trust, Usability and Knowledge Perception

Abstract: Robo-advisor has become the new personal wealth management and investment method. Nonetheless, certain predicaments are faced by robo-advisor companies as a tech-savvy young group of individuals seems to be less willing to adopt robo-advisory. This study investigates millennials’ adoption of robo-advisory in terms of financial knowledge, trust and usability perception in the 21st century to enhance sustainability. This quantitative study focuses on individuals belonging to the millennial generation who were bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…They further proved that expertise influences the acceptance of automated advice more than trust. Yi et al (2023) pointed out the importance of trust, but also financial knowledge and usability perception. Bruckes et al (2019) found that a high intention of using robo-advisors was positively influenced by structural assurance and trust in analyzed technological solution.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…They further proved that expertise influences the acceptance of automated advice more than trust. Yi et al (2023) pointed out the importance of trust, but also financial knowledge and usability perception. Bruckes et al (2019) found that a high intention of using robo-advisors was positively influenced by structural assurance and trust in analyzed technological solution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the literature on the subject, there are few works devoted to the analysis of factors shaping the attitude towards robo-advisory. However, most of them focus on a relatively narrow group of determinants in relation to the technological and operational aspects of the service (Sabir et al, 2023;Nguyen et al, 2023) and the issue of trust in this technology (Yi et al, 2023;Nourallah et al, 2023) with less attention paid to consumer characteristics and experiences.…”
Section: Introductionmentioning
confidence: 99%
“…The literature emphasizes the significance of consumer age and technological competences [27], as well as financial knowledge, literacy and experience [28][29][30]. Some studies demonstrate the importance of trust in the technologies used in robo-advisory and the providers of robo-advisory [4,[31][32][33][34][35][36], as well factors related to risk acceptance [37][38][39]. Limitations to the acceptance of robo-advisory services were also pointed out, related to reluctance to make decisions made by machines, especially when they contain an ethical component [40].…”
Section: Introductionmentioning
confidence: 99%
“…The findings grouped into three recurrent vital themes: the factors influencing Robo-Advisors' acceptance (lack of trust in AI and data security), the role of digital skills in implementation were identified and explored, highlighting their significance and interconnectedness within the context of the South African financial landscape, and these will be discussed below. (Sabir et al, 2023;Yi et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Adopting robo-advisors hinges significantly on two primary factors: lack of trust and data security (Yi et al, 2023). Concerns arise from potential risks associated with AI algorithms, raising doubts about the trustworthiness and reliability of decisions made by AI-powered systems, which, in turn, impact the acceptance of robo-advisors (Belanche et al, 2019;Mhlanga, 2021b;Shanmuganathan, 2020).…”
Section: Table 1: Summary Of Themesmentioning
confidence: 99%